ASPEK KEADILAN ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN (Studi Kecamatan Nguter Kabupaten Sukoharjo) - Zullaika Tipe Nurhidayah; Lego Karjoko (Jurnal Repertorium, 2017)
AbstractThis articel find and analyze the legislation of the implementation of the conversion of agricultural land to non-agricultural industrial area Nguter in Sukoharjo regency to balance the interests of food and industry sector. Further study on the justice aspects of the conversion of agricultural land to non-agricultural areas of Nguter Industrial Area in Sukoharjo Regency in balancing the interests of the food and industrial sectors. The research method used is normative which is peskriptif with approach of Act (statue approach). To know and analyze used among others the principle of legality, theory of bureaucratic theory stuffen, and theory of justice. The results showed that the national legislation is sufficient in balancing the agricultural sector and industrial sector, but in terms of local policy with the local regulation number 14 of 2011 on the spatial plan and Regulation of Sukoharjo Regent No. 67 of 2011 on Space Utilization Permit still unable to balance the agricultural sector as well as the industrial sector. Implementation of agriculture land conversion to nonagricultural areas Nguter Industrial Estate has not fully fulfilled the justice aspect as it tends to increase economic growth from industrial development, although the amount of rice production tends to increase but as population growth keeps increasing and agricultural land keeps decreasing significantly, come food needs can not be fulfilled.Keywords: conversion of agricultural land, justice aspect; Spatial Plan; food; industry AbstrakArtikel ini bertujuan untuk mengetahui dan menganalisis peraturan perundang-undangan pelaksanaan alih fungsi lahan pertanian ke non pertanian Kawasan Industri Nguter di Kabupaten Sukoharjo untuk menyeimbangkan kepentingan sektor pangan dan industri. Kajian selanjutnya mengenai aspek keadilan pelaksanaan alih fungsi lahan pertanian ke non pertanian Kawasan Industri Nguter di Kabupaten Sukoharjo dalam menyeimbangkan kepentingan sektor pangan dan industri. Metode penelitian yang digunakan adalah normatif yang bersifat peskriptif dengan pendekatan Undang-Undang (statue approach). Untuk mengetahui dan menganalisis digunakan antara lain prinsip legalitas, teori stuffen teori birokrasi, dan teori keadilan. Hasil penelitian menunjukan bahwa peraturan perundang-undangan secara nasional sudah cukup dalam menyeimbangkan sektor pertanian dan sektor industri, namun dari segi kebijakan daerah dengan adanya peraturan daerah nomor 14 tahun 2011 tentang rencana tata ruang wilayah dan Peraturan Bupati Sukoharjo Nomor 67 tahun 2011 tentang Izin Pemanfaatan Ruang masih belum mampu untuk menyeimbangkan sektor pertanian maupun sektor industri. Pelaksanaan alih fungsi lahan pertanian ke non pertanian Kawasan Industri Nguter belum sepenuhnya memenuhi aspek keadilan karena lebih cenderung meningkatkan pertumbuhan ekonomi dari pembangunan industri, meskipun jumlah produksi padi cenderung meningkat namun karena pertumbuhan penduduk terus meningkat dan lahan pertanian terus menurun secara signifikan, maka di di masa datang kebutuhan pangan bisa tidak terpenuhi.Kata Kunci: alih fungsi lahan pertanian; aspek keadilan; Rencana Tata Ruang Wilayah; pangan; industri.